SMART KAMPUS: Perspektif Baru Enterprise Architecture STMIK Bumigora Mataram Berbasis TOGAF ADM - Anthony Anggrawan; Christofer Satria; Husain Husain (Jurnal Mantik Penusa, 2009)
The need and progress of Information and Communication Technology (ICT), which has been developing faster and faster, needs business needs such as technology, systems, processes and communication in educational organizations ranging from systems to hardware and software supported by software and software. organization. Corporate architecture, asking about what components in the organization run business processes, organizational accountability, planning work platforms and planning, so that it can facilitate planning that is in line with the organization that is running in a structured manner. Enterprise Architecture works on blueprints or blueprints for systems that will be built or that will be developed. Problems that often occur include: decision making that is not based on information, information that is available is irrelevant, information that is not used by management, information that is not timely, too much information, information available is inaccurate, there is duplication of data, and the existence of data the way to use it is not flexible. To overcome this, this research will create a new corporate architecture in accordance with business architecture, data architecture, application architecture, Technology architecture will produce a blueprint. With the existence of Enterprise Architecture (EA) which is expected to provide explanations and requested between business and information technology, the baseline architecture and target architecture will be discussed so that harmony between business strategies and ICTs will be created. In implementing research using TOGAF ADM in planning and development of ICT and the creation of a smart campus at STMIK Bumigora Mataram.